2015
DOI: 10.3133/ds907ds
|View full text |Cite
|
Sign up to set email alerts
|

Estimated annual agricultural pesticide use for counties of the conterminous United States, 2008–12

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprod.To order this and other USGS information products, visit http://store.usgs.gov.Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 3 publications
(10 reference statements)
0
62
0
Order By: Relevance
“…In Ohio, the use of neonicotinoids rapidly increased after 2004 when they became widely used on corn and soybeans (92,93). The mechanistic link between neonicotinoid insecticides and insect declines is established and observational studies have shown widespread impacts of their use (9496).…”
Section: Discussionmentioning
confidence: 99%
“…In Ohio, the use of neonicotinoids rapidly increased after 2004 when they became widely used on corn and soybeans (92,93). The mechanistic link between neonicotinoid insecticides and insect declines is established and observational studies have shown widespread impacts of their use (9496).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated county-level glyphosate application (percentage of corn and soybeans sprayed; glyApp j,t ) in Illinois from 1994-2012 from data on glyphosate purchases and land cover from the U.S. Geological Survey (USGS; Stone 2013, Baker andStone 2015). We used the 2012 values for 2013 because these data were unavailable post-2012.…”
Section: Summer Land Cover and Land Use Datamentioning
confidence: 99%
“…Changing herbicide practices in central North America have largely eliminated milkweed hostplants from agricultural field crops, with fairly consistent, low levels of milkweed on the landscape starting from about 2003-2005(Zaya et al 2017. Although glyphosate tolerant soybeans and maize were introduced to the US market in 1996 and 1998 respectively (Duke and Powles 2009), actual glyphosate use lagged behind, with dramatic increases in use of the pesticide in 1998-2003 in soybean, and 2007-2008 in maize (Baker 2017).…”
Section: Monarch Butterflies In Mexican Overwintering Groundsmentioning
confidence: 99%